Visibilization of people with disabilities in Cúcuta: Seeking an inclusive city - Vanegas Sáenz, Héctor Daniel; Rodríguez Peña, Alejandra del Mar (DIXI, 2022)
Introduction: The concept of social inclusion is linked to that of equity, since it allows the empowerment, linkage and participation of all people in the social, economic and political life of the country. Ensuring that people with disabilities achieve full integration, recognize their potential and are not pigeonholed in their deficit is a commitment that must be supported by the country’s public policies, which should encourage cultural transformation. Methodology: During 2017 and 2018, two inclusion fairs were organized in which different institutions of the city of Cúcuta working for people with disabilities and ten private companies were invited. In the second version of the fair, a survey was applied to 465 people attending, giving a descriptive and deductive approach to the study. Results: There is a great acceptance of the concept of labor inclusion on the part of those surveyed, since more than 98% of them expressed their agreement with providing job opportunities to people with disabilities. Conclusions: This project has contributed to the identification of points to be reviewed in order to carry out social and labor inclusion processes for people with disabilities.